A política municipal de economia solidária em Maricá: avanços e desafios - Silva, Tatiane Benites da (2022)
Solidarity Economy in Brazil began to spread in the 1990s, but it was from 2003 onwards that it reached its peak in terms of national public policies, even gaining its own secretariat. In Maricá, a municipality belonging to the metropolitan region of the state of Rio de Janeiro, solidarity economy policies emerged in 2013 with the creation of the Municipal Program for Popular Solidarity Economy, Combating Poverty and Sustainable Development. Since then, the municipality has stood out, through its policies, such as the creation of the community bank; payment of social benefits in its own currency, Mumbuca; through the implementation of free municipal public transport, the vermelhinhos; as well as through policies in the area of agroecology (As HortasComunitárias) and in the area of education with the MumbucaFuturo Program, which seeks to provide training to students of elementary school II in Solidarity Economy. In this work, we present a descriptive analysis of these policies, seeking to present their potentialities and contradictions, based on field observations and interviews with managers and public servants and with the target population of the policy. We observed that the great differential of this policy, compared to others implemented in the country, was the local development strategy, allocating a good part of the municipal public fund in programs aimed at the population's quality of life, through the creation of a community bank at the municipal scale, linked to a broad income transfer policy and a local social currency.